Comparative effects of arbuscular mycorrhizal fungi on mercury translocation and growth of Ipomoea reptans Poir - Harso, Wahyu; Imanuel , Natasya Nadya; Lambui, Orryani; Prismawiryanti; Suwitra, I Ketut (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Ipomoea reptans is a widely consumed vegetable in Indonesia, but it is known as a hyperaccumulator of mercury, posing a risk to human health. The use of arbuscular mycorrhizal (AM) fungi has the potential to inhibit mercury translocation from roots to shoots, although comparative studies among AM fungal species remain limited. The study aimed to evaluate various types of AM fungi that have the potential to inhibit mercury translocation in shoot tissues and to analyze the effect of AM fungi on the growth of I. reptans in mercury-contaminated soil. The type of research is experimental research. I. reptans was either uninoculated or inoculated with Acaulospora tuberculata, Glomus sp., mixed inoculum among Acaulospora, Glomus, Gigaspora, and Scutelospora and then grown in soil with mercury contamination of 0, 4, and 8 mg Hg/kg dry soil. Plants were harvested 35 days after showing, and the phosphorus and mercury content in the shoot were determined using a UV-Vis spectrophotometer and AAS, respectively. Plant growth data and phosphorus content in the shoot were analyzed using two-way ANOVA. The results showed that AM fungi application enhanced plant growth by increasing shoot dry weight and leaf area. Inoculation with A. tuberculata and Glomus sp. reduced mercury concentration in shoots, with the lowest level observed under A. tuberculate alone, while mixed inoculum increased mercury uptake. Overall, A. tuberculata showed strong potential as an amelioration agent for sustainable agriculture on heavy metal-contaminated soil, although further molecular and field studies are necessary.